Regional odontodysplasia in early childhood: A clinical and histological study - Gondim Juliana, O. [UNESP]; Hermes, Pretel [UNESP]; Ramalho Lizeti, T. O. [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Giro Elisa, M. A. [UNESP] (Wolters Kluwer, 2009)
Regional odontodysplasia (RO) is a rare disorder of dental development. The affected teeth are clinically hypoplastic and hypocalcified, presenting a ghost-like appearance radiographically. The aim of this work was to report a clinical case of a child with both primary and permanent dentition affected by RO. The conducted therapy was based on a conservative approach, which consisted of follow-up clinical evaluations of the anomalous teeth. However, the endodontic treatment of the primary incisors failed. Then, the chosen option for patient rehabilitation became extraction followed by removable of prosthesis confection. The extracted teeth were processed for histological analysis. In spite of the uncertain prognosis, but taking into account the psychological aspects of the patient, a conservative approach in an attempt to maintain those viable teeth in the oral cavity should be established.
Keywords: Ghost teeth; Odontodysplasia; Permanent dentition; Primary dentition; canine tooth; case report; congenital malformation; deciduous tooth; dentin; differential diagnosis; enamel; follow up; human; incisor; infant; male; tooth malformation; tooth pulp; Cuspid; Dental Enamel; Dental Pulp Cavity; Dentin; Diagnosis, Differential; Follow-Up Studies; Humans; Incisor; Infant; Male; Tooth, Deciduous